Camera antipode : Ans Westra : photography as a form of ethnographic & historical writing : a dissertation presented in partial fulfilment of the degree of Doctor of Philosophy, Social Anthropology Programme, School of People, Environment & Planning, Massey University, Manawatu - McDonald, Lawrence (Massey University, 2012)
Camera Antipode: Ans Westra: Photography as a Form of Historical and Ethnographic Writing is a study of the career of the New Zealand social documentary photographer Ans Westra. It covers the period from her arrival in New Zealand from the Netherlands in 1957 right up until her most recent projects. The emphasis throughout is on Westra as a cross-cultural photographer whose work is best understood within various historical contexts and as a form of ethnographic and historical representation in its own right. The dissertation has two parts. Part One, Isagogics, consists of three chapters that deal with a range of general issues that have shaped Westra’s work and contribute to an understanding of its character. All three serve to situate Westra within multifarious conceptual frameworks and institutional contexts and establish the historical, cultural and intellectual field from which her creative project has emerged. The seven chapters of Part Two, Exegesis, provide detailed readings of Westra’s photographic books, taking in both her large-scale projects aimed at a general readership and her Bulletins and photographic essays for use in schools. Part Two proceeds chronologically and is divided into the decades of the 1960s, the 1970s, and the 1980s and on up to the present. A set of appendices follows Part Two. The first is a transcript of an interview with Ans Westra, the second a biographical chronology of her life and career, the third a list of her one-person and group exhibitions, and the fourth a set of photographs that are discussed in the text. Following the consolidated notes and references section is a bibliography in two parts: the first part is a complete list of Westra’s published works, which constitutes the primary sources of the dissertation, followed by a fraction of the secondary sources – books, articles, and reviews of Westra’s publications and exhibitions; the second part of the bibliography contains all non-Westra references cited.
Appendix of images removed for copyright reasons
Keywords: Ans Westra; Criticism and interpretation; Documentary photography; Ethnology; New Zealand; Social life and customs; History